Self-Made Woman A Memoir - Chanterelle DuBois, Denise (The University of Wisconsin Press, 2017)
Denise Chanterelle DuBois's transformation into a woman wasn't easy. Born as a boy into a working-class Polish American Milwaukee family, she faced daunting hurdles: a domineering father, a gritty 1960s neighborhood with no understanding of gender nonconformity, trouble in school, and a childhood so haunted by deprivation that neckbone soup was a staple. Terrified of revealing her inner self, DuBois lurched through alcoholism, drug dealing and addiction, car crashes, dangerous sex, and prison time. Dennis barreled from Wisconsin to California, Oregon, Canada, Costa Rica, New York, Bangkok, and Hawaii on a joyless ride. Defying all expectations, DuBois didn't crash and burn. Embracing her identity as a woman, she remade herself. Writing with resolute honesty and humor, she confronts both her past and her present to tell an American story of self-discovery.